2021
DOI: 10.21203/rs.3.rs-328364/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emission sources, Characteristics and risk assessment of particulate bound Polycyclic Aromatic Hydrocarbons (PAHs) from traffic sites

Abstract: Atmospheric PM2.5 size particulate-associated Polycyclic Aromatic Hydrocarbons (PAHs) were analyzed from December 2018 to May 2019 over three traffic sites of Chota Nagpur Plateau (CNP) of India were analyzed to study their temporal and seasonal variations. Over the last few decades, CNP becomes a hotspot of air pollution due to traffic and anthropogenic activities. The PM2.5 concentration was higher than the value given by the National Ambient Air Quality (NAAQ) standard value. The results show the total aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…To address this issue, the adoption of clean-production methods using new energy sources such as photovoltaic and nuclear powers. Moreover, efforts should be made to reduce biomass combustion from coal, petroleum, farmland grass and wood, as well as to control traffic-related oil and gas emissions [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue, the adoption of clean-production methods using new energy sources such as photovoltaic and nuclear powers. Moreover, efforts should be made to reduce biomass combustion from coal, petroleum, farmland grass and wood, as well as to control traffic-related oil and gas emissions [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Source apportionment studies of measured air pollutants, such as black carbon, PM 2.5 , and PM 10 , have revealed that the major emission sources of these pollutants are influenced by factors including industrial production, vehicular exhaust, and biomass burning [59][60][61]. The spatial distribution of these different emission sources has varying impacts on regional air quality.…”
Section: Poi Datamentioning
confidence: 99%
“…Atmospheric pollutants fall onto the marine surface through dry deposition and wet deposition processes [33]. Dry deposition involves the physical, chemical, and biological processes by which atmospheric pollutants fall onto the marine surface, while wet deposition involves ionic pollutants and soluble pollutants from the air falling onto the marine surface through precipitation or water vapor condensation [34]. The evaluation of marine atmospheric pollution deposition is mainly conducted based on the "Technical Regulations for the Assessment of the Flux of Atmospheric Pollutants Deposition into the Sea (Trial)" and includes the observation of the elements nitrate, NH 4 Cl, Cu, Pb, and Zn.…”
Section: Sources and Monitoring Indices Of Marine Pollutionmentioning
confidence: 99%